Oppression of Kurdish Women: Between Patriarchy and Social Inequality - Rasyid, Mufti; Malik, Muhammad Khoirul (IJTIMAIYA: Journal of Social Science and Teaching, 2026)
This article examines the representation of oppression against Kurdish women in Honor, Daughters of Smoke and Fire, and Dahlia and Carys. It explores how patriarchy and social inequality intersect in shaping Kurdish women’s experiences as subaltern subjects. The study applies a qualitative descriptive and library research approach, using postcolonialism and intersectional feminism as analytical frameworks. The findings show that Kurdish women experience multiple forms of oppression, including language restriction, ethnic marginalization, subordination within family and society, double burdens in domestic and public spheres, honor-based violence, gender-biased moral interpretations, and racism. The article argues that these oppressions are not solely rooted in local culture but emerge from the intersection of patriarchy, migration, class inequality, ethnic discrimination, and postcolonial legacies. Literature therefore functions as a medium of social criticism that exposes systems of domination over Kurdish women’s bodies and identities.